Efficiency of Chitosan to Vibrio spp. Isolated From Diseased Black Tiger Shrimp, Penaeus monodon Fabricius in Thailand - Ong-ard Lawhavinit,; Win Surachetpong,; Benjamas Inthasri,; Nontawith Areechon, (Agriculture and Natural Resources, 2006)
Efficiency of chitosan to Vibrio spp. isolated from diseased black tiger shrimp was studied. The result showed that the Minimum Bactericidal Concentration (MBC) of chitosan is 1,000 ppm. The chitosan could be used to induce the bacteria both high and low organic matters. The effects of the inoculation size on the activities of chitosan at 1,000 ppm were 102 - 108 CFU/ml. The MBCs of chitosan tested with 47 isolated Vibrio spp. fell in the range of 1,000-10,000 ppm. The majority of the field isolated Vibrio spp. has retained susceptibility to chitosan at 1,000 ppm. In the safety test with 1 month black tiger shrimp, no shrimp died at 0.1-1.0% of chitosan but 50% experimental shrimp died at 2.0% chitosan in 96 hours. Base on the results, the 1.0% chitosan could safe use for prevention the luminescence vibriosis in black tiger shrimp culture.